2017
DOI: 10.1101/118091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CNN-based Encoding and Decoding of Visual Object Recognition in Space and Time

Abstract: Deep convolutional neural networks (CNNs) have been put forward as neurobiologically plausible models of the visual hierarchy. Using functional magnetic resonance imaging, CNN representations of visual stimuli have previously been shown to correspond to processing stages in the ventral and dorsal streams of the visual system. Whether this correspondence between models and brain signals also holds for activity acquired at high temporal resolution has been explored less exhaustively. Here, we addressed this ques… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In line with results from macaque IT, DNNs were furthermore able to explain within-category neural similarities, despite being trained on a categorization task that aims at abstracting away from differences across categoryexemplars (Khaligh-Razavi & Kriegeskorte, 2014). At a lower spatial, but higher temporal resolution, DNNs have also been shown to be predictive of visually evoked magnetoencephalography (MEG) data Cichy, Khosla, Pantazis, Torralba, & Oliva, 2016;Fritsche, G, Schoffelen, Bosch, & Gerven, 2017). On the behavioural level, deep networks exhibit similar behaviour to humans (Hong, Yamins, Majaj, & DiCarlo, 2016;Kheradpisheh, Ghodrati, Ganjtabesh, & Masquelier, 2016b, 2016aKubilius, Bracci, & Op de Beeck, 2016;Majaj, Hong, Solomon, & DiCarlo, 2015) and are currently the best-performing model in explaining human eye-movements in free viewing paradigms (Kümmerer, Theis, & Bethge, 2014).…”
Section: Brain-inspired Neural Network Models Are Revolutionising Artificial Intelligence and Exhibit Rich Potential For Computational Nesupporting
confidence: 67%
“…In line with results from macaque IT, DNNs were furthermore able to explain within-category neural similarities, despite being trained on a categorization task that aims at abstracting away from differences across categoryexemplars (Khaligh-Razavi & Kriegeskorte, 2014). At a lower spatial, but higher temporal resolution, DNNs have also been shown to be predictive of visually evoked magnetoencephalography (MEG) data Cichy, Khosla, Pantazis, Torralba, & Oliva, 2016;Fritsche, G, Schoffelen, Bosch, & Gerven, 2017). On the behavioural level, deep networks exhibit similar behaviour to humans (Hong, Yamins, Majaj, & DiCarlo, 2016;Kheradpisheh, Ghodrati, Ganjtabesh, & Masquelier, 2016b, 2016aKubilius, Bracci, & Op de Beeck, 2016;Majaj, Hong, Solomon, & DiCarlo, 2015) and are currently the best-performing model in explaining human eye-movements in free viewing paradigms (Kümmerer, Theis, & Bethge, 2014).…”
Section: Brain-inspired Neural Network Models Are Revolutionising Artificial Intelligence and Exhibit Rich Potential For Computational Nesupporting
confidence: 67%
“…Previous work has established a correspondence between hierarchy of the DCNN and the fMRI responses measured across the human visual areas (Güçlü and van Gerven, 2015; Eickenberg et al, 2016; Seibert et al, 2016; Cichy et al, 2016b). Further research has shown that the activity of the DCNN matches the biological neural hierarchy in time as well (Cichy et al, 2016b; Seeliger et al, 2017). Studying intracranial recordings allowed us to extend previous findings by assessing the alignment between the DCNN and cortical signals at different frequency bands.…”
Section: Discussionmentioning
confidence: 99%
“…frequencies). With time-resolved magnetoencephalography (MEG) recordings it has been demonstrated that the correspondence between the DCNN and neural signals peaks in the first 200 ms (Cichy et al, 2016b; Seeliger et al, 2017). Here we test the remaining dimension: that biological visual object recognition is also specific to certain frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…RSA characterizes the similarity of measured responses to experimental conditions in representational dissimilarity matrices (RDMs). As RDMs can in principle be computed for any measurement modality, RSA on MEG opens the way to quantitatively relate rapidly emerging brain dynamics to other data, such as fMRI (Cichy et al, 2016b(Cichy et al, , 2013 in order to localize responses; computational models (Cichy et al, 2017a(Cichy et al, , 2016aKietzmann et al, 2017;Pantazis et al, 2017;Seeliger et al, 2017;Su et al, 2012;Wardle et al, 2016) in order to understand the underlying algorithms and representational format; to behaviour (Cichy et al, 2017b;Furl et al, 2017;Mur et al, 2013); and across species (Cichy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%